PENGARUH PENGGUNAAN MEDIA DIORAMA TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Roudhotul Jannah; Yasir Arafat; Eni Heldayani (STKIP Subang, 2023)
This study aims to determine the effect of the use of diorama media on the science learning outcomes of grade five students of SD Negeri 17 Tanjung Batu. The research was carried out in the even semester of 2022/2023. This research uses the Experiment method with the True-Experimental Design technique in the form of a Pretest-Posttest Control Group Design. The sample in this study was class V-A students as a control class totaling 27 students, and class V-B as an experimental class totaling 23 students. The research instrument used is a written test in the form of multiple-choice questions as many as 10 questions on water cycle material. Based on the data from the results of the research that has been carried out, it can be proven from the results of the final test (posttest) in the experimental class treated with diorama media obtained an average score of 78.26 and the control class obtained an average value of 64.44. In addition, through hypothesis testing with the t-test (Independent Sample T-Test) the results obtained that the count value > is 3.681 > 2.011 which means Ha is accepted and Ho is rejected, it can be concluded that there is an influence of the use of diorama media on the science learning outcomes of grade five students of SD Negeri 17 Tanjung Batu. Keywords: Diorama Media, Science Learning Outcomes